Answer:
For the system of equations given, x = 0
Explanation:
1. Let's solve the system of equations to find out the value of x:
1st equation:
x+ 2y = 6
x = 6 - 2y (Subtracting 2y at both sides)
2nd equation:
6y = x + 18
Replacing x with the result of the 1st equation:
6y = (6 - 2y) + 18
6y = 6 - 2y + 18
6y + 2y = 18 + 6 (Adding 2y at both sides)
8y = 24
y = 24/8 = 3 (Dividing by 8 at both sides)
Now we can find out the value of x:
x + 2y = 6
x + 2 * 3 = 6
x = 6 - 6 (Subtracting 6 at both sides)
x = 0
3. Let's prove that x = 0 and y = 3 in the 2nd equation:
6y = x + 18
6 * 3 = 0 + 18
18 = 18
We proved that x = 0 and y = 3 are correct.